Critical Remarks on Some Business-Cycle Theories - Tinbergen, J. (Econometrica, 1942)
Also published in: A.H. Hansen and R.V. Clemence (Eds), Readings in Business Cycles and National Income, Allen & Unwin, London, 1953, pp. 357-375